TEACHING ENGLISH POETRY IN THE DIGITAL ERA: AN IT-BASED MODEL FOR UNIVERSITY CLASSROOMS - Nor Laili Fatmawati, M.Pd (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
The integration of Information Technology (IT) into English literature instruction has transformed the way poetry is taught and experienced in higher education. This study explores the implementation of an IT-based instructional model for teaching English poetry in Indonesian public university classrooms using a qualitative research design. Data were collected through classroom observations, in-depth interviews, and analysis of students’ digital learning artifacts, including multimedia annotations, online discussion threads, and collaborative projects. The instructional model employed digital platforms such as interactive learning management systems, multimedia annotation tools, and collaborative online forums to facilitate engagement, interpretation, and collaborative meaning-making in poetry learning. The findings indicate that the IT-based model fostered more active participation, enriched interpretive discussions, and enabled students to explore poetic meaning through multimodal representations. Students reported that digital tools enhanced their appreciation of poetic language and imagery while providing a more flexible and interactive learning environment. However, challenges were noted, including disparities in digital literacy, inconsistent internet connectivity, and the need for targeted professional development for instructors. This study concludes that qualitative insights into IT-based poetry instruction provide a nuanced understanding of how digital tools can bridge the gap between traditional literary pedagogy and contemporary learning needs in public universities.